Alleviation of trigeminal neuropathic pain by electroacupuncture: the role of hyperpolarization-activated cyclic nucleotide-gated channel protein expression in the Gasserian ganglion. Issue 3 (June 2019) - Yang, Liuyue; Ding, Weihua; You, Zerong; Yang, Jinsheng; Shen, Shiqian; Doheny, Jason T; Chen, Lucy; Li, Ruhui; Mao, Jianren
Introduction: The aim of this study was to examine the effect of electroacupuncture (EA) on trigeminal neuropathic pain in rats and explore the potential mechanism underlying the putative therapeutic effect of EA. Methods: Trigeminal neuropathic pain behavior was induced in rats by unilateral chronic constriction injury of the distal infraorbital nerve (dIoN-CCI). EA was administered at ST2 ( Sibai ) and Jiachengjiang . A total of 60 Sprague Dawley rats were divided into the following four groups ( n = 15 per group) to examine the behavioral outcomes after surgery and/or EA treatment: sham (no ligation); dIoN-CCI (received isoflurane only, without EA treatment); dIoN-CCI+EA-7d (received EA treatment for 7 days); and dIoN-CCI+EA-14d (received EA treatment for 14 days). Both evoked and spontaneous nociceptive behaviors were measured. Of these, 12 rats ( n = 4 from sham, dIoN-CCI, and dIoN-CCI+EA-14d groups, respectively) were used to analyze protein expression of hyperpolarization-activated cyclic nucleotide-gated (HCN) channel in the Gasserian ganglion (GG) by immunohistochemistry. Results: dIoN-CCI rats exhibited mechanical allodynia and increased face-grooming activity that lasted at least 35 days. EA treatment reduced mechanical allodynia and face-grooming in dIoN-CCI rats. Overall, 14 days of EA treatment produced a prolonged anti-nociceptive effect as compared to 7-day EA treatment. The counts of HCN1 and HCN2 immunopositive puncta were increased in the ipsilateral GG in dIoN-CCI rats and were reduced by 14 days of EA treatment. Discussion: EA treatment relieved trigeminal neuropathic pain in dIoN-CCI rats, and this effect was dependent on the duration of EA treatment. The downregulation of HCN expression may contribute to the anti-nociceptive effect of EA in this rat model of trigeminal neuropathic pain.